OVERVIEW ON THE RESEARCH SITUATION OF THE RIP CURRENT AT THE SEA BEACHES OF VIETNAM AND IN THE WORLD - Xuan, Nguyen Ba (Vietnam Journal of Marine Science and Technology, 2009)
This paper presents an overview of the research situation of the rip current occurred at the sea beaches of Vietnam and in the world. Through the study and evaluation of collected materials, it found that: the rip current is not a mysterious phenomenon, that is a special  component  of  the  general  current  having  the  direction  apart  from  the  coast  and usually causes the death accidents when people swimming in the coastal sea. It was formed in the surf  zone and often  be in a fluctuation, which depends on the conditions of the terrain coast, sea bottom and sea wave created by the influence of the changed weather conditions ... This paper also presents a summary of the reasons and mechanisms formatted the rip current and the methods to identify and guide how to prevent the rip currents when falling in the zone of their action.